Granulocyte Transfusion Therapy as a Bridge to Hematopoietic Stem Cell Transplant in a Child with Aplastic Anemia and Refractory Perirectal Abscess - Mary Dang; Beenish Rubbab; Jeannie Kwon; Daniel Noland; Paul K Sue; Kathryn E Dickerson (Journal of the Pediatric Infectious Diseases Society, 2023)
Abstract Background Idiopathic aplastic anemia is a rare form of bone marrow failure characterized by multilineage cytopenias and hypocellular bone marrow [A]. Persistent neutropenia is an important risk factor for the development of life-threatening infections [B]. Perirectal cellulitis and perianal abscess are associated with high rates of morbidity, and eradication of such infections in the absence of neutrophil recovery is challenging. Here we report the use of adjuvant granulocyte transfusion therapy to treat antibiotic refractory proctitis with perirectal abscess, in a child with severe aplastic anemia. Method A 7-year-old previously healthy female presented with pancytopenia in the setting of Human Meta-pneumovirus and Parainfluenza infection. Initial bone marrow evaluation revealed mildly hypocellular bone marrow (60-70%) with granulocytic and megakaryocytic hypoplasia. Flow cytometry did not reveal malignancy, and her pancytopenia progressed to transfusion dependence. Two months following initial presentation, she presented with rectal pain and febrile neutropenia (ANC< 200/mm) requiring admission for IV antibiotics. She defervesced on piperacillin-tazobactam, and was discharged to home with negative blood culture, but one week later, re-presented with recurrence of fever and worsening perirectal pain, and evidence of proctitis without abscess on abdominal CT scan. A repeat bone marrow evaluation showed progression to bone marrow aplasia. She was discharged on oral levofloxacin prophylaxis but Three days later, developed hematochezia and fevers, with evidence of proctitis with perirectal abscess on MRI. She was started on vancomycin and meropenem and discharged home on outpatient piperacillin-tazobactam to complete at least a14-day course. The patient was subsequently readmitted on day 15 of therapy with new fevers and persistent proctitis on CT scan. Given her persistent proctitis despite 2 weeks of antibiotic therapy, a trial of granulocyte infusion therapy was administered from days 22-26 and 31-32 Abdominal CT on day 33 showed improvement in anorectal inflammatory changes and decreased size of perianal fluid collection. She was subsequently discharged home on IV piperacillin-tazobactam with a plan to continue parenteral antibiotic therapy until evidence of radiographic cure. One week later, she was noted to have rising inflammatory markers, with evolving proctitis on interval CT, leading to readmission on day 46 for fever and worsening pain despite IV antibiotics. HSCT was deferred until resolution of her infection. Combination therapy consisting of granulocyte infusions with continued antimicrobials was initiated, and she received an additional 10-day course of granulocytes with piperacillin-tazobactam Results Patient subsequently demonstrated resolution of fevers, declining CRP, and radiographic resolution of perirectal abscess and proctitis. She was cleared for transplant and underwent Haplo-identical related BMT without recurrence of infection. Conclusion We report the successful use of granulocyte transfusion with antimicrobials to treat antibiotic refractory proctitis, in a child with profound neutropenia. In our case, infection persisted despite prolonged antimicrobial therapy with resolution only after an extended course of granulocyte transfusion. In the setting of stable but refractory bacterial perianal infection, granulocyte transfusion therapy in conjunction with antibiotics should be considered in profoundly neutropenic patients without anticipated count recovery. Discussion Perirectal cellulitis and perianal abscess are a frequent complication of hematologic malignancies and are associated with significant morbidity and mortality in the neutropenic patient. Management is particularly challenging in the absence of neutrophil count recovery, with high rates of recurrence, morbidity and mortality associated with surgical incision and drainage [C] and significant failure rates with medical therapy alone. High-dose granulocyte transfusion therapy has been proposed as an adjunct to antibiotic therapy in such settings, but evidence for clinical efficacy remains limited [D]. A systemic review [E] in 2015 was unable to clarify standard use of granulocytes nor clearly shown a survival benefit to their use. In the same year, the RING randomized controlled trial was also published [D]. Unfortunately, RING was underpowered due to low enrollment and there was no (P>0.99 intention to treat, P=0.64 with treatment) mortality difference at 42 days. Post hoc analysis showed patients receiving a high dose (>0.6 x 109 per kg) did significantly better than low dose patients (but not controls). More recent single center studies/series [F] in pediatrics have shown safety and efficacy locally in retrospective analysis. Granulocyte transfusion is currently considered when patients have neutropenia (<500/uL), bacterial or fungal infection not responding to antimicrobials, and a reasonable expectation of neutrophil recovery [H]. As was required by our transfusion medicine service, we chose to attempt a proscribed (10-day) rather than open-ended treatment course (ten daily doses) of granulocyte transfusion in this patient with a known response to allow for entry into HSCT for treatment of her underlying disease. Here we report the successful use of granulocyte transfusion in conjunction with antimicrobials to treat antibiotic refractory proctitis, in a child with profound neutropenia. In our case, infection persisted despite prolonged antimicrobial therapy with evidence of radiographic and clinical resolution only after an extended course of granulocyte transfusion. As our patient was awaiting HSCT for definitive treatment of her very severe idiopathic aplastic anemia, there was no expectation of imminent bone marrow recovery, with clearance of her infection following granulocyte transfusion allowing her to proceed to transplant. In the setting of stable but refractory bacterial perianal infection, the use of granulocyte transfusion therapy in conjunction with antibiotics should be considered among profoundly neutropenic patients without anticipated count recovery. References A.Wilson DB, Link DC, Mason PJ, Bessler M. Inherited bone marrow failure syndromes in adolescents and young adults. Ann Med. 2014 Sep;46(6):353-63. doi: 10.3109/07853890.2014.915579. Epub 2014 Jun 3. PMID: 24888387; PMCID: PMC4426964. B.Valdez JM, Scheinberg P, Young NS, Walsh TJ. Infections in patients with aplastic anemia. Semin Hematol. 2009 Jul;46(3):269-76. doi: 10.1053/j.seminhematol.2009.03.008. PMID: 19549579. C.Baker B, Al-Salman M, Daoud F. Management of acute perianal sepsis in neutropenic patients with hematological malignancy. Tech Coloproctol. 2014 Apr;18(4):327-33. doi: 10.1007/s10151-013-1082-z. Epub 2013 Nov 26. PMID: 24276114. D.Price TH, Boeckh M, Harrison RW, McCullough J, Ness PM, Strauss RG, Nichols WG, Hamza TH, Cushing MM, King KE, Young JA, Williams E, McFarland J, Holter Chakrabarty J, Sloan SR, Friedman D, Parekh S, Sachais BS, Kiss JE, Assmann SF. Efficacy of transfusion with granulocytes from G-CSF/dexamethasone-treated donors in neutropenic patients with infection. Blood. 2015 Oct 29;126(18):2153-61. doi: 10.1182/blood-2015-05-645986. Epub 2015 Sep 2. PMID: 26333778; PMCID: PMC4626256. E.Estcourt LJ, Stanworth SJ, Hopewell S, Doree C, Trivella M, Massey E. Granulocyte transfusions for treating infections in people with neutropenia or neutrophil dysfunction. Cochrane Database Syst Rev. 2016 Apr 29;4(4):CD005339. doi: 10.1002/14651858.CD005339.pub2. PMID: 27128488; PMCID: PMC4930145. F.Kagızmanlı GA, Guzelkucuk Z, Işık P, Kara A, Ozbek NY, Yarali N. Efficacy and safety of granulocyte transfusion in children: A single-center experience. J Clin Apher. 2020 Sep;35(5):420-426. doi: 10.1002/jca.21818. Epub 2020 Jul 28. PMID: 32722895. G.Cushing MM, Poisson JL. Blood transfusion therapy: a handbook. Bethesda: AABB, 2020 Figure 1. Figure 2 A.Initial CT scan pf pelvis showing proctitis B.First follow up CT scan with improvement after initial granulocyte trial C.Second follow up CT scan with evolving proctitis after 6-week course of antibiotics alone D.Third follow up CT scan after second granulocyte course showing complete resolution of proctitis